Polish Migrants In Sweden: An Overview - Lubińska, Dorota (Folia Scandinavica Posnaniensia, 2013)
The current Polish migrant group in Sweden is the largest in Scandinavia, and experienced a significant growth after the enlargement of the European Union in 2004. The present overview is an attempt to give a systematic picture of this group, and is based on a selection of publications from a larger bibliography. The bibliography was compiled by the author in order to survey the knowledge on Polish migrants in Sweden, and is attached to this overview. The overview is primarily confined to the period between 1940 and 1990 because this period is covered by the scholarly literature.